2007
DOI: 10.1369/jhc.7a7312.2007
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of a Novel Collectin CL-K1 in Murine Tissues

Abstract: We have recently identified a novel collectin, CL-K1, that may play a role in innate immunity as a member of the collectin family. In this study using mice, we investigated the tissue distribution of CL-K1 for better understanding of its pathophysiological relevance. Real-time PCR analyses demonstrated that CL-K1 mRNA was expressed in all tissues tested. Immunohistochemical analyses demonstrated that CL-K1 was expressed in proximal tubules of kidney, in mucosa of the gastrointestinal tract, and in bronchial gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 32 publications
1
24
0
Order By: Relevance
“…Complement activation that proceeds through MASP-2 but does not subsequently require C4 has been reported in several organ models of stress-induced injury including postischemic injury of the heart, intestine, and kidney (26,27). Since CL-11 is expressed within these organs (3,4,11), it is possible that CL-11-mediated lectin pathway activation underpins a common trigger mechanism. In contrast to CL-11, we found no evidence to support a significant role of MBL in our model, since complement deposition on cells largely failed when CL-11 was absent, even though MBL was present (in serum) in our experiments.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Complement activation that proceeds through MASP-2 but does not subsequently require C4 has been reported in several organ models of stress-induced injury including postischemic injury of the heart, intestine, and kidney (26,27). Since CL-11 is expressed within these organs (3,4,11), it is possible that CL-11-mediated lectin pathway activation underpins a common trigger mechanism. In contrast to CL-11, we found no evidence to support a significant role of MBL in our model, since complement deposition on cells largely failed when CL-11 was absent, even though MBL was present (in serum) in our experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma concentration of CL-11 (12,13) is approximately one-tenth the concentration reported for MBL (2 μg/ml), albeit in a different study population (14). In addition, whereas MBL mainly originates by hepatocyte synthesis (15), CL-11 is synthesized at multiple tissue sites including the liver, brain, and heart, as well as in those systems cited above (3,4,11).…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…CL-K1 is expressed primarily by cells in the adrenal gland, kidney, and liver. Our previous studies using mainly recombinant CL-K1 indicated that it largely forms monomers and dimers of individual subunits, although larger oligomers were also detected in the circulation (6,12,16). Recently, it was shown that defects in human CL-K1 or MASP-3 are strongly associated with a defect related to midline development called 3MC syndrome (17,18), and these findings suggest a role for complement components in developmental processes.…”
mentioning
confidence: 99%